Innovation in Learning Applications Based on the Adaptive Inquiry Approach as a Means to Enhance Students' Critical Thinking Skills - Musdalifah Nihaya; Nurhilaliyah Nurhilaliyah; Harun Nihaya; Nurhidayat Nurhidayat (Education and Talent Development Center Indonesia (ETDC Indonesia), 2026)
This study aims to develop a draft of a learning application based on the Adaptive Inquiry Approach, which integrates inquiry models with learning style adaptive systems and to evaluate the product's feasibility and its evaluation instrument characteristics. This study employed a Research and Development (R&D) approach using the Luther-Sutopo development model, restricted up to the initial product and instrument testing stage. The subjects for the instrument testing were 4th–6th-grade students at Muhammadiyah Bantaeng Elementary School. Data were analyzed using descriptive quantitative techniques to calculate the feasibility interpretation index and empirical analysis of the test items (discriminatory power and difficulty level). Expert validation indicated that the product draft is highly feasible, with average interpretation indices of 82.50% from model concept experts, 86.00% from learning technology experts, 83.13% from design and graphics experts, and 81.82% from learning style experts. The characteristics testing of the mathematics test instruments demonstrated good empirical quality, where all pre-test and post-test items achieved a discrimination coefficient of (good category) and a difficulty index within the ideal range ( P ). Supporting materials, including the model guidebook and teacher's guide, were also declared highly feasible, with average validation scores exceeding 81%. The draft of the learning application based on the Adaptive Inquiry Approach and its evaluation instruments have been proven theoretically and empirically valid and reliable, making it highly feasible to proceed to the large-scale implementation phase to measure students' critical thinking skills.